The Limits of Nationalist Politics: Electoral Culture and Mobilization in Germany, 1890-1903 - Fairbairn, Brett (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractWith Germany's unification, nationalism became an entrenched part of the political culture, until its role was challenged by the rise of social “fairness” issues in the 1890s. In the first decades of the Reich, campaigns against minorities like Catholics, Poles, and Social Democrats helped cement the progovernmental forces, especially in intense “national” elections. The Kartell elections of 1887, in particular, created a patriotic coalition that remained a significant factor in electoral politics for over twenty years. But in the 1890s, nationalist coalition-building became increasingly difficult as the Kartell parties lost support, drifted apart, and competed more and more with one another. The government made efforts to shore up its allies, but these efforts failed to halt the disintegration. Significantly, while some argued the government should use the naval issue or the tariff issue (Sammlungspolitik) to influence the elections of 1898 and 1903, the government was unable to do so. Instead, increasing electoral support went to the parties that were perceived as '“mass” parties, especially the Catholic Centre and Social Democrats. These parties organized social-interest constituencies by appealing to “fairness” issues like suffrage, civil liberties, and fair taxation.